2018
DOI: 10.1038/s41564-018-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Host-linked soil viral ecology along a permafrost thaw gradient

Abstract: Climate change threatens to release abundant carbon that is sequestered at high latitudes, but the constraints on microbial metabolisms that mediate the release of methane and carbon dioxide are poorly understood. The role of viruses, which are known to affect microbial dynamics, metabolism and biogeochemistry in the oceans, remains largely unexplored in soil. Here, we aimed to investigate how viruses influence microbial ecology and carbon metabolism in peatland soils along a permafrost thaw gradient in Sweden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
663
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 466 publications
(723 citation statements)
references
References 63 publications
53
663
7
Order By: Relevance
“…Although we did not test the ecological and evolutionary consequences of variation in viral diversity in this study, it is probable that some members of the vampire bat viral community identified here have functional importance. For example, viral metagenomics has identified specific viral taxa associated with disease (Duerkop et al, 2018;Hannigan, Duhaime, Ruffin, Koumpouras, & Schloss, 2018;Ly et al, 2014;Norman et al, 2015) and the critical contributions of certain viral groups to overall ecosystem function (Emerson et al, 2018;Sunagawa et al, 2015;Thurber, Payet, Thurber, & Correa, 2017). Follow-up analyses could include targeting individual viral taxa that are linked with health or disease in other systems, examining associations between variation in viral diversity and host fitness, or testing interactions between viral communities and other components of the host microbiome.…”
Section: Viral Richnessmentioning
confidence: 99%
“…Although we did not test the ecological and evolutionary consequences of variation in viral diversity in this study, it is probable that some members of the vampire bat viral community identified here have functional importance. For example, viral metagenomics has identified specific viral taxa associated with disease (Duerkop et al, 2018;Hannigan, Duhaime, Ruffin, Koumpouras, & Schloss, 2018;Ly et al, 2014;Norman et al, 2015) and the critical contributions of certain viral groups to overall ecosystem function (Emerson et al, 2018;Sunagawa et al, 2015;Thurber, Payet, Thurber, & Correa, 2017). Follow-up analyses could include targeting individual viral taxa that are linked with health or disease in other systems, examining associations between variation in viral diversity and host fitness, or testing interactions between viral communities and other components of the host microbiome.…”
Section: Viral Richnessmentioning
confidence: 99%
“…Recent advances in metagenome sequencing have enabled high-throughput exploration of the virosphere, leading to a >200-fold increase in viral genomes available in databases, and uncovering >1,000 new genus-level viral groups (Emerson et al, 2018;Paez-Espino et al, 2016;Roux et al, 2016;Suttle, 2007). While these data provide new insights into viral genome diversity, 40 most of these uncultivated viral genomes are not associated with any host.…”
Section: Introductionmentioning
confidence: 99%
“…Emerson et al 12 predicted 14 viral glycoside hydrolase (GH) enzymes in these sequences with projected functions for breaking glycosidic linkages in pectin, hemicellulose, starch, and cellulose molecules; one of these was confirmed to express an endomannanase enzyme 12 .…”
mentioning
confidence: 99%